Overheating risk in Mediterranean residential buildings: Comparison of current and future climate scenarios - Rodrigues, Eugénio (2020)
One of the effects of climate change is global warming, which will increase cooling demand in buildings. However, scientific literature does not show consensus on the risk of highly insulated buildings being prone to overheating. This paper presents a statistical comparison of two synthetic datasets for current and future climates in sixteen Mediterranean locations. The weather data for the 2050 climate projection was generated by ‘morphing’ current weather data. The buildings were created using a generative design method to produce random geometries and random U-values for the envelope elements. Energy performance was evaluated using dynamic simulation. In addition to the expected general increase in cooling demand (up to 137 %) and a smaller reduction in heating demand (up to 63 %), the results demonstrate that the ideal U-values used in the current climate in almost all of the locations will not cause overheating. In several cases, the decrease of the U-values is even recommended for Podgorica, Valencia, Tunis, Malaga, Larnaca, and Alexandria, as the reduction of heating demand compensates the increase of cooling demand. Casablanca was the only location showing an increase in the ideal U-values, thus presenting risk of overheating if using current ideal U-values.